A fast dynamic model for a large scale heat pipe embedded latent heat thermal energy storage system for optimal sizing and control. (July 2022) - Pan, Chunjian; Vermaak, Natasha; Wang, Xingchao; Romero, Carlos; Neti, Sudhakar; Chen, Chien-Hua; Bonner, Richard
Abstract: One of the challenges to design and control phase change material (PCM) based latent heat thermal energy storage (LHTES) systems is to develop fast models to accurately represent their transient and nonlinear behaviors. In this paper, a fast explicit modeling approach for a multi-dimensional finned PCM system, called alternating front propagating, is proposed based on the concept of the alternating-direction implicit algorithm for multi-dimensional parabolic and elliptic differential equations. The proposed modeling method is employed to develop a fast explicit dynamic model for a large scale LHTES system, whose heat transfer is enhanced by imbedded circular finned heat pipes. The developed fast model has negligible computational cost and is of sufficient accuracy compared to high-fidelity numerical solutions. The fast explicit model of the LHTES system was employed in a model predictive control framework to determine the HTF flowrate so that its outlet temperature meets a target value. The controlled HTF flowrate can increase the usage efficiency of the stored heat in a LHTES system. Highlights: A reduced dynamical model based on alternating solidification fronts updating A reduced dynamical model for a large-scale LHTES system Controlled HTF mass flowrate to achieve high PCM usage efficiency